Electrical Transport in Thick Film Resistors. (1980) - Hill, Robert M.
Abstract : It is only in the last ten years or so that solid state physics has had the temerity to consider that real solids are neither perfect nor pure, whereas for many years all resistors of reasonable quality have been impure, highly doped, and clearly disordered in structure. As solid state theory has developed there have been attempts to understand the resistor problem but until now, with hindsight, we can say that the tools required have not been available. The situation is, even now, not perfectly clear but there is sufficient information available to make a critical assessment of the methods that can be applied and to indicate where the solution to the problem of carrier transport in resistor materials might lie.